Environmental variables and performance: evidence from the hotel industry in Malaysia - Awang, Khairil Wahidin; Ishak, Nor Khomar; Mohd Radzi, Salleh; Taha, Azni Zarina (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The growth and performance of the Malaysian hotel industry depend heavily on the growth and performance of the other Malaysian economic sectors, especially manufacturing and services. The recent 5 years saw the Malaysian hotel industry going through drastic changes, with regard to its external environment, largely due to the greater extent of volatility in the environment and the increasing level of uncertainties in the world’s economy. Organizational internal processes, systems and strategies should be based upon assessment of the external environment. The level of environmental uncertainties caused by global environmental turbulence was represented by an erratic rate of economic growth. In parallel, the environment can be expected to affect organizational choices because the maintenance of organizations depends upon some degree of exchange with outside partners. An organization, which depends on the environment, is not in itself a problem, as long as the flow of required resources is stable and assured. Problems arise when the flow of resources becomes uncertain due to unpredictable changes in the environment. These changes are assumed to have an immediate impact on the hotel industry’s rate of growth and performance. Logically then, there should be a relationship between the hotel industry’s performance and growth rate, measured in sales volume, with the economic growth rate (the Gross National Product). This paper identifies the relationships between external environment volatility and industry performance among the 5, 4 and 3-star hotel categories during the same period.